Factors Associated with Platelet Recovery in Dengue Patients on Fever Day 7 - Ghina Shofi Ikrima Ghina Shofi; Elfira Yusri Elfira; Fadrian Fadrian Fadrian; Efrida Efrida Efrida; Mutia Lailani Mutia; Yustini Alioes Yustini (Frontiers on Healthcare Research, 2026)
Background: Thrombocytopenia is a common hematological feature of dengue infection, and platelet recovery is a reliable prognostic indicator. The seventh day of fever typically marks the beginning of the recovery phase, but some patients show delayed platelet recovery. This study aimed to identify the factors affecting platelet recovery in adult dengue patients on fever day 7. Methods: This cross-sectional study was conducted from April 2024 to April 2025 at Universitas Andalas Hospital and involved 35 adult dengue patients selected through total sampling. Retrospective data on clinical and laboratory characteristics were collected. Platelet recovery was defined as an increase in platelet count of more than 20,000/mm³ within 48 hours between fever days 5 and 7. Patients who received platelet transfusion or corticosteroid therapy were excluded. Associations between variables were analyzed using the Chi-square test and Fisher’s Exact Test. Results: A significant association was found between platelet recovery and thrombocytopenia status at admission (p = 0.037). Age, sex, comorbidity, hematocrit level, leukocyte count, and day of fever at admission were not significantly associated with platelet recovery (p > 0.05). Only 10 of the 35 patients (28.6%) showed platelet recovery on fever day 7. Most patients were male (57.1%) and aged ≤40 years (80.0%), while 22.9% had comorbidities. Conclusion: Thrombocytopenia status at hospital admission was significantly associated with platelet recovery in dengue patients. Early recognition of this factor may help identify clinically at-risk patients and enable more effective clinical management.